Pagluklok sa diwa the case of Iglesia Catolica de la Nuestra Senora de la Escalera Church ruins in Nasugbu, Batangas - Vasquez, Harvey A. (College of Architecture, University of the Philippines Diliman, 2017)
The research proponent's main goal is to reinstall the importance of the Lumang Simbahan church ruins through a multi-disciplinary approach that will eventually result in the proper restoration and commemoration of the site. The study is the first step in the multi-stage process that begins in the proper evaluation of the current perception of the stakeholders of Nasugbu, Batangas on the importance of the Lumang Simbahan church ruins. This evaluation will then be the leading instrument in devising the recommendations of policies and programs for the eventual commemoration of the Lumang Simbahan church ruins. The research proponent through field research and community engagements confirm that the stakeholders of Nasugbu, Batangas have the necessary recognition of the importance of the Lumang Simbahan church ruins, but currently lack the proper understanding on what makes the Lumang Simbahan church ruins important to the town of Nasugbu, Batangas. The proper understanding of the importance of the Lumang Simbahan church ruins is crucial in it's sustained awareness as it will ensure the inter generational transfer of the collective consciousness of its importance. Given the present date from the months of September to November in the year 2017 compiled by the research proponent, the recommended policies, programs, and architectural intervention posited in this study is present in the commemoration and the re-installation of the Lumang Simbahan church ruins as an important local heritage site for the town of Nasugbu, Batangas.